Advances on the prevention of cancers attributed to infectious agents: Avances En La Prevención De Cánceres Atribuidos A Agentes Infecciosos - Alburqueque Melgarejo, Joseph (2020)
Currently, cancers of infectious origin, represent a public health problem, especially in emergent countries. After its discovery more than 50 years ago, arduous efforts have been made to identify the agents involved, their routes of transmission and their carcinogenesis mechanisms, in order to develop effective prevention measures.